The Role of Inflammation in the Pathogenesis of Preeclampsia - Michał Michalczyk; Aleksander Celewicz; Marta Celewicz; Paula Woźniakowska-Gondek; Rafał Rzepka (Hindawi Limited, 2020)
Preeclampsia (PE) affects 5-8% of pregnant women, and it is the major cause of perinatal morbidity and mortality. It is defined as arterial hypertension in women after 20 weeks of gestation which cooccurs with proteinuria (300 mg/d) or as arterial hypertension which is accompanied by one of the following: renal failure, liver dysfunction, hematological or neurological abnormalities, intrauterine growth restriction, or uteroplacental insufficiency. Currently, pathophysiology of preeclampsia poses a considerable challenge for perinatology. Preeclampsia is characterized by excessive and progressive activation of the immune system along with an increase in proinflammatory cytokines and antiangiogenic factors in fetoplacental unit as well as in vascular endothelium in pregnant women. A single, major underlying mechanism of preeclampsia is yet to be identified. This paper discusses the current understanding of the mechanisms which underlie the development of the condition. Some significant factors responsible for PE development include oxidative stress, abnormal concentration and activity in mononuclear phagocytic system, altered levels of angiogenic and antiangiogenic factors, and impaired inflammatory response triggered by inflammasomes. Detailed understanding of pathophysiology of inflammatory process in PE can largely contribute to new, targeted anti-inflammatory therapies that may improve perinatal outcomes in PE patients.